Cardiovascular, behavioral, and psychological responses to organizational prodiversity messages among racial/ethnic minorities. (December 2021) - Dover, Tessa L.; Major, Brenda; Kaiser, Cheryl R.
Despite the widespread assumption that prodiversity values make companies more attractive workplaces for underrepresented groups, few experiments have tested this assumption. Two experiments investigated the impact of prodiversity messages in organizational recruitment materials for racial/ethnic minorities. In Study 1 ( N = 399), racial/ethnic minority MTurk workers imagined applying for a position at a prodiversity (vs. neutral) company, then imagined receiving acceptance or rejection feedback. In Study 2 ( N = 179), Latino men engaged in a realistic hiring simulation while cardiovascular and behavioral responses were recorded. They then received acceptance or rejection feedback. Both experiments found that the presence (vs. absence) of prodiversity messages had no significant effect on anticipated belonging, anticipated fairness, or concerns about discrimination at the company. Study 2 also found that the presence (vs. absence) of prodiversity messages had no effect on interview performance or on cardiovascular responses during the interview. Moreover, following feedback, the presence (vs. absence) of prodiversity messages led participants to attribute their feedback more to illegitimate factors, and to rate themselves as less competent/deserving. Implications for organizations and minority job candidates are discussed.